IMPROVING STUDENTS' LISTENING SKILL THROUGH STORYTELLING APPLICATION IN SMK NEGERI 5 SAMARINDA - Abdul Rohman (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
Learning that uses technology in the form of learning applications that are used as a means for teachers and students to facilitate the learning process that aims to achieve the success of a learning and also create an effective learning atmosphere, learning by using mobile learning media can make students interesting and fun. The researcher took one of the learning application technologies that could be useful for students to achieve English language learning, especially in listening, which was the story telling application. This application can be downloaded via Google Play Store and can be used by students to explain or describe listening skills in English. This application provides various interesting stories with English vocabulary and pronunciation that are easily understood by Indonesian students. The objective of this study is to find out is there any effect of Improving Students' Listening Skill Through Storytelling Application in SMK Negeri 5 Samarinda. This research used Classroom Action Research (CAR). The result showed that the use of storytelling applications to improve the listening skills of class XI students of SMK Negeri 5 Samarinda was successful. The students were very enthusiastic when the researcher asked the students to fill in the worksheet with questions to complete the story together